Analysis of the Dynamic Load Sharing Characteristic of Two-stage Planetary Transmission - Li Siqian; Wu Shijing; Wang Xiaosun (Jixie chuandong)
To study the dynamic load sharing characteristics of two- stage planetary gear train,a translation- torsion coupling dynamics model is established by taking the nonlinear factors like time- varying mesh stiffness,position error,eccentric error,gear backlash and coupling stiffness into account,and the dimensionless dynamics differential equations for the system are derived and solved by numerical method. The effects of floating components,planetary gear error and coupling stiffness on the load sharing characteristics are analyzed.The research work has guiding significance for the design of multi- stage planetary gear train,and the reference basis for the research of dynamics analysis and dynamic load sharing characteristic of two- stage planetary gear is provided.